Curcumin as a potential inhibitor of TGFβ3 computational insights for breast cancer therapy - Ali G. Alkhathami; Mohammad Y. Alshahrani; Saad Ali Alshehri; Nazim Nasir; Shadma Wahab (Scientific Reports)
Abstract Previous research indicates that Transforming growth factor beta-3 (TGFβ3) expression levels correlate with breast cancer metastasis, and elevated TGFβ3 levels have been linked with poor overall survival in breast cancer patients. The study used computational methods to examine curcumin’s effects on TGFβ3, a chemical with antiviral and anticancer characteristics. The curcumin has low Molecular Weight 368.130 (MW) and follows Lipinski Rule, Pfizer Rule, GSK Rule, Golden Triangle, BMS Rule, zero PAINS alert and Acute Toxicity Rule with zero alert. Any drug-like contender must follow these qualities. Through molecular docking analyses, curcumin displayed favourable binding affinities at the TGFβ3 binding pocket, forming key interactions such as hydrogen bonds with residues like ASP323, ARG325, VAL333, HIS334, PRO336, LYS337, GLY393, and ARG394. 500 ns molecular dynamic simulations examined docking interactions. Molecular dynamics (MD) simulations trajectories analysis, by calculating lower structural deviation, minimal residual fluctuations, structural compactness assessment by calculating radius of gyration, surface area calculation which interact with solvent, role of hydrogen bonding, and secondary structural analyses. Furthermore, principal component, Gibbs free energy landscape and MMPBSA analysis, signifying system stability. These data suggest curcumin may inhibit TGFβ3, providing a framework for developing new compounds targeting this protein.